Evaluating the Therapeutic Efficacy of Mono- and Bivalent Affibody-Based Fusion Proteins Targeting HER3 in a Pancreatic Cancer Xenograft Model - Leitao Ch. D. Charles Dahlsson; Rinne S. S. Sara; Altai M. Mohamed; Vorontsova O. Olga; Dunas F. Finn; Jonasson P. Per; Tolmachev V. M. Vladimir Maksimilianovich; Lofblom J. John; Stahl S. Stefan; Orlova A. M. Anna Markovna (2020, 2020)
Title screen